Kajian Senyawa Bioaktif Dari Tumbuhan Obat Tradisional Kulit Akar Tumpunik (Artocarpus rigida BI) - Farid, Faizar (Biospecies, 2010)
This study aims to isolate and identify bioactive compounds contained in the root of tumpunik (Artocarpus rigida BI). The root was firstly extracted using ethanol and then continued with fractionation process using a solvent combination of hexane, chloroform, ethyl acetate, and methanol. The obtained fractionate then was tested its toxicity towards shrimp A Salina larvae. The results show that soxhletation with methanol solvent could produce 36.5 grams of concentrated extract (7.30% of sample weight). Meanwhile, soxhletation using hexane fractionates, chloroform, ethyl acetate, and methanol produces 3.4 grams, 6.9 grams, 9.3 grams, and 16 grams of concentrated extract respectively. The LC50 (ppm) after three-hour toxicity test are 780, 367, 136, and 845 respectively.